Growing vegetables : all the know-how and encouragement you need to grow and fall in love with! your brand-new food garden - Sowards, Jessica (First-time gardener., 2021)
Growing Vegetables (The First-Time Gardener) is an essential tool for newbie gardeners, handing them all the practical and inspirational know-how they need to grow a fruitful garden, even if its their very first time sinking a seed into the soil. Planting your first vegetable garden can be intimidating; it's tough to know where to start. Before you sink your hands into the soil, you want answers to all of those questions rolling around inside your head. In Growing Vegetables (The First-Time Gardener), you'll find the answers you're looking for. Where do I put my new garden? How do I prepare the soil? What vegetables should I plant? Is it better to start new plants from seed or should I buy transplants? What about watering, feeding, and taking care of my garden? What do I do if bugs show up? Homesteader Jessica Sowards, the warm and vivacious host of YouTube's Roots and Refuge Farm, is the perfect teacher for new gardeners, offering not just know-how but inspiration and time-management tips for success. Not only will you learn how to prepare, plant, and tend your first vegetable garden, you'll also learn how to design an eco-friendly layout, how to grow with the seasons, and how to maximise your harvest, even if you only grow in a small space. Jessica wants your first food-growing experience to be a positive one, and she's prepared to go the distance to make sure tending the earth becomes your new favourite hobby. There are no stupid questions here. Everyone has to start somewhere, after all. A single growing season is all it takes to fall in love with growing your own healthy, organic, nutrient-dense food. With Jessica as your guide, you'll soon discover all the satisfactions, challenges, and great joys of growing your own food garden.